Revision of the spider genus Heteropoda (Sparassidae: Heteropodinae) from Laos - Jäger, Peter; Nophaseud, Liphone; Moradmand, Majid (Zootaxa, 2026)
The genus Heteropoda from Laos is revised. Thirteen new species are described from three species groups. H. amphora-group: H. bormee sp. nov. (male, female) from Vang Vieng (vegetation, cave), H. hiphi sp. nov. (female) from Oudomxai Province (cave), H. longkou sp. nov. (female) from Houaphan province (cave). H. helge-group: H. bolaven sp. nov. (male, female) from Champasak province (leaf litter), H. buang sp. nov. (male, female) from Bolikhamsay province (leaf litter), H. lata sp. nov. (male, female) from Luangprabang province (cave), H. namtha sp. nov. (male, female) from Luang Namtha (vegetation, leaf litter). H. tetrica-group: H. bang sp. nov. (male, female) from Khammouan province (leaf litter), H. hmong sp. nov. (male, female) from Vientiane province, Vang Vieng (slopes, walls, vegetation, etc.), H. kading sp. nov. (male, female) from Bolikhamsay province (leaf litter), H. khem sp. nov. (female) from Bolikhamsay province (cave), H. phoukha sp. nov. (female) from Luang Namtha province (cave), H. vangvieng sp. nov. (male, female) from Vientiane Province, Vang Vieng (vegetation along limestone cliffs, caves). Modified diagnoses are given for the H. helge-, H. tetrica-, and H. amphora-groups. Some species are affiliated with species groups for the first time: H. helge-group: H. pilata Korai & Jäger, 2024a; H. simplex-group: H. aemulans Bayer & Jäger, 2009, H. boutani (Simon, 1906), H. maxima Jäger, 2001a, H. opo Jäger, 2014, H. simoneallmannae Jäger, 2018; H. tetrica-group: H. schwendingeri Jäger, 2005. New records are given for H. maxima, H. aemulans, H. schwalbachorum Jäger, 2008, the latter two species are illustrated. H. vangvieng sp. nov. and H. aemulans were caught by a pompilid wasp. For the junior primary homonym Heteropoda hainanensis Korai & Jäger, 2024b, preoccupied by H. hainanensis Li, 1991, the new substitute name Heteropoda acies nom. nov. is proposed. The type material of H. venatoria (Linnaeus, 1767) is determined to be female. A COI-based phylogeny provides strong support for the distinctiveness of five of the newly described Heteropoda species (H. bang sp. nov., H. buang sp. nov., H. hmong sp. nov., H. lata sp. nov., H. namtha sp. nov.).